An explorative study of factors associated with treatment in specialized mental health care centers among GP patients in Norway - Ole Gunnar Tveit; Torleif Ruud; Ketil Hanssen-Bauer; Ole Rikard Haavet; Ajmal Hussain (BMC, 2021)
Abstract Background Effectiveness and efficiency are part of the quality of care for mental health problems, and treatment should thus be performed at the right level of care. Norwegian guidelines specify which patients should be given priority for treatment in specialized mental health care (SMHC) centers, but there is a lack of agreement on which patients should actually receive SMHC. In this study we wanted to examine what factors (patient and GP characteristics) were related to GP patients who received treatment in SMHC centers. Methods In this retrospective cohort study, we looked at 12 months of data from electronic health records from six GP and SMHC centers of hospitals in the catchment area. We included all patients who had been treated at any of the GP centers during the 12-month period (N=18032). We fit a generalized linear mixed model to explore which factors were related to patients receiving treatment in SMHC centers. Further exploration was performed to study the effects of gender and contact frequency. Results We found that 4.6% of all GP patients and 18.4% of the GP patients with a mental health problems were treated in SMHC centers. There were more women than men among the GP-patients (56% vs 44%) and in SMHC centers (55% vs 45%), women with mental health problems were more severely ill than men. However, after adjusting for other factors men were more likely to be treated in SMHC centers (OR: 1.44). Patients with frequent GP contact were more likely to be treated in SMHC centers. The GP characteristics age, gender and specialization did not relate to patients receiving treatment in SMHC centers. Conclusions Men were more likely to be treated in SMHC centers than women, which may imply that they have different thresholds for entering SMHC centers. GP characteristics were not related to receiving treatment in SMHC centers. More specific knowledge is needed to determine whether men and women currently receive treatment at the lowest possible level of care.